Are the oxygen isotopic compositions of Fitzroya cupressoides and Nothofagus pumilio cellulose promising proxies for climate reconstructions in northern Patagonia? - Lavergne, Aliénor (2016)
Tree ring δ18O chronologies from two native species (Fitzroya cupressoides and Nothofagus pumilio) in northern Patagonia were developed to assess their potential for paleoclimate reconstructions. The five annually resolved cellulose δ18O chronologies (two for F. cupressoides and three for N. pumilio) are located on the Andes along the steep west-to-east precipitation gradient. Over the common 60 years long interval, the five site-δ18Ocell chronologies exhibit a strong common signal as indicated by the significant mean intercorrelation (r = 0.61, p < 0.05) and the high percentage (65%) of total variance explained by the first empirical orthogonal function. Although correlation analyses reveal that the two mean species-δ18Ocell chronologies are mainly modulated by December-May temperature, the N. pumilio chronology shows a greater sensitivity to record temperature variations (r = 0.57, p < 0.05). The δ18Ocell of N. pumilio contains a regional temperature signal representative of a large area in southern South America under the influence of the Southern Annular Mode. This study indicates that δ18Ocell in N. pumilio is a promising proxy to reconstruct past variations in temperature in South America south of 38°S.